Reinstatement of Metatarsonemus attiah (Acari: Tarsonemidae), with description of a new species, redefinition of the genus and a key to the world species - Lofego, Antonio Carlos [UNESP]; Cavalcante, Ana Cristina Cerqueira; Demite, Peterson Rodrigo; Rezende, José Marcos [UNESP]; Ochoa, Ronald; de Moraes, Gilberto José (Magnolia Press, 2019)
A new species, Metatarsonemus caissara Lofego & Cavalcante sp. nov., is described based on females and males collected on Eugenia umbelliflora O. Berg. (Myrtaceae) from Atlantic Forest areas of São Paulo State, Brazil. Metatarsonemus Attiah is reinstated as a genus based on apomorphic attributes which are recovered through examination of specimens of the new species herein described, in addition to specimens of M. simplicissimus Attiah and M. megasolenidii Lofego & Ochoa. A cladistic analysis tentatively indicates that the Metatarsonemus lineage is sister group to a lineage comprising the genera complex Daidalotarsonemus+Ceratotarsonemus+Excelsotarsonemus in sharing four homoplasious apomorphic attributes. A dichotomous key is provided for identification of the species of this genus described so far.
Keywords: Atlantic Forest; Brazil; Myrtaceae; Tarsonemidae classification